Ultrafast nonlinear silicon waveguides and quantum dot semiconductor optical amplifiers - Vallaitis, Thomas (Karlsruhe Series in Photonics & Communications / Karlsruhe Institute of Technology, Institute of Photonics and Quantum Electronics (IPQ), 2011)
In this book, nonlinear silicon-organic hybrid waveguides and quantum dot semiconductor optical amplifiers are investigated. Advantageous applications are identified, and corresponding proof-of-principle experiments are performed. Highly nonlinear silicon-organic hybrid waveguides show potential for all-optical signal processing based on fourwave mixing and cross-phase modulation. Quantum dot semiconductor optical amplifiers operate as linear amplifiers with a very large dynamic range.